Analisis Faktor-Faktor Masyarakat Terhadap Keputusan Beralih ke Televisi Digital - Mauly Putri; Hery Supiarza; Salsa Solli Nafsika (Jurnal EMT KITA, 2023)
Analog Switch Off or ASO is a process of stopping analog broadcasts from switching to digital television broadcasts. According to the decision of the government authority, ready or not, the public must switch to digital television, even though the exposure to information and the level of knowledge about digital television is low. Through the Theory of Diffusion of innovation by Everett M. Rogers, attempts to analyze the factors of society switching to Digital Television. This study used a quantitative method with a questionnaire to the Jatihurip Village community. The aim of this research is to find out the differences in demographic profiles between users and non-users of Digital Television, the use of media as a communication channel, and the factors of switching to Digital Television. The data analysis technique uses multiple linear regression analysis, with the test results showing that innovation opportunities, the number of campaigns, and following technology have a positive and significant effect on the decision to switch to Digital Television for the people of Jatihurip Village, Sumedang Utara District. The Innovation Opportunity factor greatly influences the decision to switch to digital television for the people of Jatihurip Village, Sumedang Utara District.